Efficacy and safety of dimethylfumarate in elderly psoriasis patients: a multicentric Italian study. (19th May 2022) - Ricceri, Federica; Bardazzi, Federico; Buggiani, Gionata; Burlando, Martina; Campione, Elena; Corazza, Monica; Cuccia, Aldo; Dapavo, Paolo; Filippi, Federica; Zichichi, Leonardo; Parodi, Aurora; Prignano, Francesca
Abstract: The number of psoriatic elderly patients is steadily increasing in the Western world, nevertheless they are frequently excluded from clinical trials and described as a high-risk group for adverse events. We conducted a retrospective multicentric study of DMF use in elderly (>65 years) psoriatic patients. DMF efficacy was evaluated up to 24 weeks by Psoriasis Area and Severity Index (PASI) score. We also evaluated drug maintenance and safety. Our study population included 81 elderly psoriatic patients treated with DMF up to 24 weeks. The PASI score at the baseline (week 0) ranged from 3, 7–24 (mean ± SD, 9, 8 ± 4, 1), which changed after DMF administration to 4, 3 ± 3, 2 at week 16 and 2, 7 ± 3, 2 at week 24. Among 81 elderly psoriatic patients 59 (72, 8%) adverse events were reported during the observation period. The most common were gastrointestinal complaints ( n  = 24, 29, 6%) and flushes ( n  = 10, 12, 3%). Lymphocytopenia ( n  = 10, 12, 35%) was frequently observed. In daily practice, DMF seems to be efficacy and well tolerated in elderly psoriatic patients. DMF may be a first-line systemic treatment option to manage elderly psoriasis, provided that also the long-term safety data are closely monitored, in particular lymphocytopenia.